2018
DOI: 10.1108/mhrj-09-2017-0039
|View full text |Cite
|
Sign up to set email alerts
|

The role of mental health nurses in supporting young people’s mental health: a review of the literature

Abstract: Purpose -Adolescent mental health issues are on the increase, in particular depression, which is now a major public health concern globally. Mental health education is important and young people's awareness of mental health is potentially limited. This is one factor that creates barriers to seeking support. School nurses and educational professionals recognise that they do not necessarily have the required skill base to support emotional health concerns with young people. The purpose of this paper is to synthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 57 publications
0
4
0
2
Order By: Relevance
“…The sense of worry described by Jönsson et al (2019) and Pryjmachuk et al (2011) recognizes that school nurses may not trust their knowledge or they may feel that they lack the emotional competence to manage students who are struggling or having an acute mental health need. In fact, a need for additional training or education in youth mental health assessment and care is well documented (Arnold & Baker, 2018;Bartlett, 2015;Ravenna & Cleaver, 2016). It remains critical to implement professional development programs that provide school nurses with evidence-based training on assessing and managing students with mental health needs, as well as programs that school nurses can deliver to students to prevent mental health problems.…”
Section: Discussionmentioning
confidence: 99%
“…The sense of worry described by Jönsson et al (2019) and Pryjmachuk et al (2011) recognizes that school nurses may not trust their knowledge or they may feel that they lack the emotional competence to manage students who are struggling or having an acute mental health need. In fact, a need for additional training or education in youth mental health assessment and care is well documented (Arnold & Baker, 2018;Bartlett, 2015;Ravenna & Cleaver, 2016). It remains critical to implement professional development programs that provide school nurses with evidence-based training on assessing and managing students with mental health needs, as well as programs that school nurses can deliver to students to prevent mental health problems.…”
Section: Discussionmentioning
confidence: 99%
“…It was found, however, that professionals find obstacles to perform an effective service, especially in relation to the reduced team and the non-involvement of the university’s professionals to effectively recognize and face psychological distress. It is postulated that university management should pay close attention to key points that need to be rethought and discussed, both regarding physical infrastructure and organizational aspects and human resource quantity and qualification ( 3 , 6 ) .…”
Section: Discussionmentioning
confidence: 99%
“…For an effective approach to this mental health problem, it is recommended to ensure that students have opportunities to experience mental health promotion actions in the university context and, when seeking assistance due to the possibility of psychological distress, they are welcomed in an accessible and comfortable environment with duly trained and problem-solving professionals ( 6 ) .…”
Section: Introductionmentioning
confidence: 99%
“…In conclusion, good relationships with siblings and regular meetings with friends should be promoted among adolescents by parents and all other adults. It has also been suggested that adolescents benefit from the possibility of regular meetings with healthcare professionals such as school nurses or mental health nurses (Arnold & Baker, 2018). Mental health promotion by mental health nurses in comprehensive schools might be a good start for increasing positive mental health (Onnela et al, 2014).…”
Section: Discussionmentioning
confidence: 99%